355 COMPOUND FIELD POTENTIALS VARY WITH INNERVATION OF THE PREGNANT RAT CERVIX. (1st January 2005) - Buth-Fisher, E. P.; Haugen, T. W.; Osborne, S. V.; Maeda, G.; Tran, L.; Yellon, S. M.; Kirby, M. A.
Abstract : Previously we have demonstrated that innervation of rodent cervix is increased before birth, a process also described in humans. The objective of this study was to determine the physiological contribution of neural input to the cervix from the vagus, hypogastric, and pelvic nerves. Pregnant (D19-D21), post-partum, and non-pregnant Sprague-Dawley rats were anesthetized with Nembutal (40mg/kg), injected intraperitoneally, and paralyzed with Gallamine triethiodide (2mg/kg) and/or Pancuronium bromide (2mg/kg). Animals were maintained on artificial respiration then dissected using a midline incision to expose the abdominal viscera. The vagus (subdiaphram), hypogastric and pelvic nerves were isolated then stimulated using a bipolar electrode. Signals were recorded from the cervix using a concentric bipolar electrode (Fred Haer Inc-CBEEJ75) connected to an ETH-250 Bioamplifier (CB Sciences). Field potentials were then analyzed with MacLab 4e using Chart 3.6. Nerve conduction velocities were in the range of slow unmyelinated C-afferent pain fibers. The current required to reach threshold was, in general, larger in non-pregnant and post partum groups than in late term pregnant rats. In non-pregnant, post-partum and pregnant rats respectively, threshold potentials were 30 mA, 30 mA, and 5 mA for the vagus, 20-, 18-, and 2 mA for the hypogastric and 30-, 20-, and 0.1 mA for the pelvic nerves. These observations raise the possibility that reduced thresholds of cervical field potentials reflect increased innervation to the cervix before birth. This increase in cervical innervation may contribute to the cervical ripening essential for parturition. Supported by a generous grant form the John Mace Pediatric Grant and the Dean of the School of Medicine.